Achieving Learning Outcomes through Drama: An Action Research - Kumari, Neeraj (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The introduction of Learning Outcomes has been a marvelous step to mark the students on the learning continuum. It would be inappropriate to assess the children on the basis of a pen paper test taken at the end of the term. The expected learning outcomes developed for Classes I to VIII help the teachers to take the right path of teaching-learning. It also helps the teacher to keep a check on the improvements made by the learner. The present action research is regarding the achievement of learning outcomes of Hindi language by Class- I students of a Delhi government school. The difficulty they face in this regard has been the root cause of this research. The research also tries to put forth a possible method to achieve the learning outcomes. This paper tries to explore the potential of Drama. Drama is used to help the students achieve more than they could do earlier. Many drama exercises and activities are used in the classroom situation by the action researcher to achieve the learning outcomes time and again over a period of time in an academic session. Through observations, group discussions, class work and reflective diaries, the inferences have been drawn after cross analysing the data.